A movement disorder specialist gets a taste of his own medicine. (December 2020) - van Gerpen, Jay A.; Middlebrooks, Erik H.; Tipton, Philip W.
Abstract: We present a case in which a movement disorder neurologist developed two different hyperkinetic movements due to corticospinal tract hyperexcitability, which resolved completely with surgical removal of an epidural spinal canal tumor. The first-hand description of these movements creates a unique opportunity for enhanced insight into these complex movement phenomena.